Presence of magnesium-alumina spinel in forsterite ceramics and its influence during sintering and on resulting properties of fired body. (June 2019) - Nguyen, M; Sokolář, R
Abstract: The main objective of this paper is to describe the creation and behaviour of magnesium-alumina spinel (MA-spinel) phase from raw materials mixtures in forsterite refractory and its influence on resulting physical properties and mineralogical composition of fired body. Forsterite ceramics is mostly used for its high refractoriness as a refractory material in kilns and furnaces and also in electrotechnical engineering for its high coefficient of linear thermal expansion for ceramic-metal joints. Currently, forsterite is not produced in the Czech Republic. The primary objective is to synthesize forsterite ceramics via solid-state reaction utilizing various raw materials used in industry with stoichiometric ratio of forsterite. The resulting properties of fired body will be determined using X-ray diffraction analysis for mineralogical composition, thermal dilatometric analysis and vacuum water absorption method for physical properties of fired body and refractoriness of pyrometric cones will be conducted.